Micronutrient Deficiencies Are Common in 6- to 8-Year-Old Children of Rural Nepal, with Prevalence Estimates Modestly Affected by Inflammation. Issue 6 (17th April 2014) - Schulze, Kerry J.; Christian, Parul; Wu, Lee S.-F.; Arguello, Margia; Cui, Hongjie; Nanayakkara-Bind, Ashika; Stewart, Christine P.; Khatry, Subarna K.; LeClerq, Steven; West, Keith P.
Abstract: Subclinical micronutrient deficiencies remain a hidden aspect of malnutrition for which comprehensive data are lacking in school-aged children. We assessed the micronutrient status of Nepalese children, aged 6 to 8 y, born to mothers who participated in a community-based antenatal micronutrient supplementation trial from 1999 to 2001. Of 3305 participants, plasma indicators were assessed in a random sample of 1000 children. Results revealed deficiencies of vitamins A (retinol <0.70 μ mol/L, 8.5%), D (25-hydroxyvitamin D <50 nmol/L, 17.2%), E (α-tocopherol <9.3 μ mol/L, 17.9%), K (decarboxy prothombin >2 μ g/L, 20%), B-12 (cobalamin <150 pmol/L, 18.1%), B-6 [pyridoxal-5′-phosphate (PLP) <20 nmol/L, 43.1%], and β-carotene (41.5% <0.09 μ mol/L), with little folate deficiency (6.2% <13.6 nmol/L). Deficiencies of iron [ferritin <15 μ g/L, 10.7%; transferrin receptor (TfR) >8.3 mg/L, 40.1%; TfR:ferritin >500 μ g/ μ g, 14.3%], iodine (thyroglobulin >40 μ g/L, 11.4%), and selenium (plasma selenium <0.89 μ mol/L, 59.0%) were observed, whereas copper deficiency was nearly absent (plasma copper <11.8 μ mol/L, 0.7%). Hemoglobin was not assessed. Among all children, 91.7% experienced at least 1 micronutrient deficiency, and 64.7% experienced multiple deficiencies. Inflammation (α-1 acid glycoprotein >1 g/L, C-reactive protein >5 mg/L, or both) was present in 31.6% of children, affecting the prevalence of deficiency as assessed by retinol, β-carotene, PLP, ferritin, TfR, selenium, copper, or having any or multiple deficiencies. For any nutrient, population deficiency prevalence estimates were altered by ≤5.4% by the presence of inflammation, suggesting that the majority of deficiencies exist regardless of inflammation. Multiple micronutrient deficiencies coexist in school-aged children in rural Nepal, meriting more comprehensive strategies for their assessment and prevention.